1987
DOI: 10.1016/s0735-1097(87)80356-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of verapamil on experimental cardiomyopathy in the Bio 14.6 Syrian hamster

Abstract: The Bio 14.6 Syrian hamster provides a good model for experimental study of cardiomyopathy. Cardiac receptor binding sites (alpha-1-, beta- and calcium antagonists) were studied in early (21 days old) and late (70 days old) stages of cardiomyopathy. The effects of verapamil on histologic features and free radicals in the heart were studied. The number of alpha-1- and beta-cardiac receptor binding sites was significantly greater in the late stage of cardiomyopathy when compared with findings in normal golden ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…Various early studies have shown beneficial effects of verapamil in the cardiomyopathic hamster that carries a deletion within the δ-sarcoglycan gene (17,18). Here we also demonstrate beneficial effects of verapamil on the cardiomyopathic phenotype in a more genetically defined mouse model deficient for δ-sarcoglycan.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Various early studies have shown beneficial effects of verapamil in the cardiomyopathic hamster that carries a deletion within the δ-sarcoglycan gene (17,18). Here we also demonstrate beneficial effects of verapamil on the cardiomyopathic phenotype in a more genetically defined mouse model deficient for δ-sarcoglycan.…”
Section: Introductionsupporting
confidence: 74%
“…The beneficial use of verapamil has been shown extensively in a variety of diseases such as hypertension and cardiac arrhythmias, as well as in humans and animal models with cardiomyopathy (17,18,22,23). Interestingly, the cardioprotective efficacy of verapamil was attributed to increased transmural blood flow related to vasodilation of the coronary artery bed (17,22) as well as to the potential of verapamil to inhibit membrane calcium influx into cardiomyocytes (18). The current data reveal new compelling evidence that perturbed vascular function and intermittent ischemiclike events play a significant role in the pathogenesis of cardiomyopathy in Sgcb-and Sgcd-null mice.…”
Section: Discussionmentioning
confidence: 99%
“…A relation between fibrous tissue and arrhythmias also may have therapeutic implications. Treatment with angiotensin-converting enzyme inhibitors and calcium antagonists has been shown to limit the development offibrosis in animal models ofcardiomyopathy (9,(75)(76)(77). Therefore, inhibition of collagen infiltration with failure to develop nonuniform propagation might be one mechanism by which these agents reduce mortality in animals with cardiomyopathy (9,78) and humans with congestive heart failure (79,80).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined changes in the density ofthe Ca2+ antagonist receptor of the a, subunit of the dihydropyridine (DHP)-sensitive Ca2+ channel (Ca2+ channel) in the myocardium from cardiomyopathic hamsters (21)(22)(23)(24), rats with pressure overload (25,26) or infarction (27) and patients with idiopathic dilated cardiomyopathy (28,29) and hypertrophic cardiomyopathy (30). In these diverse animal models and human diseases there have been conflicting findings on the abundance of DHP binding sites (reviewed in reference 3 1 ).…”
Section: Introductionmentioning
confidence: 99%